Perception of Sharia SME Towards PSAK 101 in Bangka Belitung Islands Province - Ulyah, Himmatul; Rudianto, Nur Ahmad Ricky (Manunggal Halim Jaya, 2025)
This research aims to descriptively analyze the level of concern that Sharia SME (halal certified SME) in Bangka Belitung Province has regarding PSAK 101. The data collection method used a questionnaire which was distributed to 78 respondents and only 53 respondents filled in completely and were used as sample. The results of the research show that as many as 38% of respondents understand PSAK 101, and the remaining 62% do not understand PSAK 101. The perception of usefulness is that with standardized guidelines in sharia MSME financial reporting, it will make it easier for the financial reports to be understood to be the highest average while the difficulty of employing Qualified accountants have the highest average perception of uselessness. Even though this research is only a descriptive analysis and does not test a hypothesis, it is hoped that this research can increase our knowledge insight and can become a background for increasing understanding of PSAK 101 for Sharia SME in the future, as well as research material that can be studied further comprehensively.